MAKING SOLID URBAN HOUSBHOLD WASTE MANAGEMENT BY COMMUNITY FINANCIALLY FEASIBLE THROUGH PUBLIC POLICY SUPPORT: A CASE STUDY FROM THE CITY OF BOGOR (Membuat Pengelolaan Sampah Padat Rumah Tangga Perkotaan Berbasis Komunitas Layak Secara financial Melalui) - Manuntun Parulian Hutagaol (Pusat Studi Lingkungan Hidup Universitas Gadjah Mada, 2009)
ABSTRACTThis study aims at evaluating financial feasibility of the business of household solid waste management by cooperative as a communal-based organization and to formulate a set ofpublic policy required to support this business. The study was carried in the communities of Rlll 8 and RW I3 of the Bubulak Sub-district of Bogor City. The study reveals that this business is financially feasible to implement. However, its financial feasibility is largely dependent on the government's support delivered through a variety of public policies. They include: (a) provision of special credit scheme to provide a free-interest rate loan to finance initial investment required to establish a communitybased household solid waste management through cooperative (b) provision of cost subsidization policy for the processing of organic solid waste into fertilizing compost products (c) replacement of the existing policy that provide subsidy for use of manufactured fertilizers for rice production with policy that provide subsidy for use of fertilizing compost products to encourage development of market for compost products in Java.ABSTRAKStudi ini bertujuan untuk mengevaluasi kelayakan financial dari usaha pengelolaan sampah padat rumah tangga perkotaan oleh koperasi yang berbasis komunitas dan merumuskan kebijakan public yang dibutuhkan untuk mendukung pelaksanaan bisnis tersebut. Studi dilaksanakan di RW 8 dan RW 13 Kelurahan Bubulak, Kota Bogor. Studi menunjukkan bahwa usaha pengelolaan sampah padat berbasis masyarakat secara finasial layak untuk dilaksanakan. Namun kelayakan ini sangat tergantung pada dukungan pemerintah melalui berbagai kebijakan pulik. Kebijakan yang dibutuhkan untuk mendukung kelayakan finasial usaha berbasis masyarakat ini adalah: (a) kebijakan skim kredit yang menyediakan pinjaman lunak bebas bunga untuk membiayai investasi awal yang dibutuhkan untuk membangun suatu bisnis pengelolaan sampah berbasis komunitas melalui koperasi, (b) Kebijakan subsidi biaya pengolahan sampah padat organic menjadi pupuk kompos, (c) mengganti kebijakan subsidi penggunaan pupuk pabik oleh petani padi dengan kebijakan subsidi penggunaan pupuk kompos untuk mendorong pengembangan pasar pupuk kompos di Jawa.